Longitudinal assessment of microbial dysbiosis, fecal unconjugated bile acid concentrations, and disease activity in dogs with steroid‐responsive chronic inflammatory enteropathy. (7th April 2019) - Guard, Blake C.; Honneffer, Julia B.; Jergens, Albert E.; Jonika, Michelle M.; Toresson, Linda; Lawrence, Yuri A.; Webb, Craig B.; Hill, Steve; Lidbury, Jonathan A.; Steiner, Joerg M.; Suchodolski, Jan S.
Abstract: Background: Mounting evidence from human studies suggests that bile acid dysmetabolism might play a role in various human chronic gastrointestinal diseases. It is unknown whether fecal bile acid dysmetabolism occurs in dogs with chronic inflammatory enteropathy (CE). Objective: To assess microbial dysbiosis, fecal unconjugated bile acids (fUBA), and disease activity in dogs with steroid‐responsive CE. Animals: Twenty‐four healthy control dogs and 23 dogs with steroid‐responsive CE. Methods: In this retrospective study, fUBA were measured and analyzed. Fecal microbiota were assessed using a dysbiosis index. The canine inflammatory bowel disease activity index was used to evaluate remission of clinical signs. This was a multi‐institutional study where dogs with steroid‐responsive CE were evaluated over time. Results: The dysbiosis index was increased in dogs with CE (median, 2.5; range, −6.2 to 6.5) at baseline compared with healthy dogs (median, −4.5; range, −6.5 to −2.6; P = .002) but did not change in dogs with CE over time. Secondary fUBA were decreased in dogs with CE (median, 29%; range, 1%‐99%) compared with healthy dogs (median, 88%; 4%‐96%; P = .049). The percent of secondary fUBA in dogs with CE increased from baseline values (median, 28%; range, 1%‐99%) after 2‐3 months of treatment (median, 94%; range, 1%‐99%; P = 0.0183). Conclusions and Clinical Importance: These findings suggest that corticosteroids regulate fecal bile acids in dogs with CE. Additionally, resolution of clinical activity index in dogs with therapeutically managed CE and bile acid dysmetabolism are likely correlated. However, subclinical disease (i.e., microbial dysbiosis) can persist in dogs with steroid‐responsive CE.